Kemampuan Karbon Aktif Kulit Durian (Durio Zibethinus Murray) Sebagai Media Filter Terhadap Bau Dan Zat Organik Pada Air Sumur Gali - Inayah, Inayah; Ady, Patriot Irvana (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2024)
One of the important physical parameters in determining whether or not water is suitable as a source of clean water is odor and organic substances. Organic substances contained in water can come from nature itself or the effects of human activities. Based on preliminary tests carried out, it was found that the organic substances in the dug well water that were examined were 61.80 mg/l, thus exceeding the quality standards of Minister of Health Regulation No. 32 of 2017, organic substances are permitted at 10 mg/l. This type of research is experimental. The aim of the research is to determine the ability of durian peel activated carbon as a filter media for odors and organic substances in dug well water at the Makassar Ministry of Health Polytechnic Campus, Department of Environmental Health. Samples were studied with media thickness treatments of 7 cm, 9 cm and 11 cm. From research conducted with an initial sample of 61.80 mg/l after treatment, results were found at a thickness of 7 cm with an average of 12.72 mg/l and a reduction percentage of 79.41%, at a thickness of 9 cm with an average amounted to 6.6 mg/l and a reduction percentage of 89.31% then at a thickness of 11 cm with an average of 2.94 mg/l and a reduction percentage of 95.23%. So it can be concluded that durian peel activated carbon is able to reduce the smell and organic substances because the thicker the media used, the higher the reduction in organic substances that occurs. It is suggested that the use of durian skin can be used as an alternative in solving problems with clean water and also something to consider.  Keywords : activated carbon ; organik matter; odor ; durian skin